PENINGKATAN KEMAMPUAN GURU DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL MELALUI WORKSHOP DI SMA NEGERI 12 TANGERANG - Wowo Permana (Rausyan Fikr : Jurnal Pemikiran dan Pencerahan, 2022)
ABSTRACTThe purpose of this study was to improve the ability of teachers in setting minimum completeness criteria through a workshop at SMA Negeri 12 Tangerang. The research was conducted in two cycles. In each cycle through 4 stages of planning, implementation, observation and reflection. The research subjects were teachers at SMA Negeri 12 Tangerang. And the object of this school action research is the teacher's ability to set minimum completeness criteria. The results showed that the teacher's ability to set minimum completeness criteria through coaching in the form of a workshop at SMA Negeri 12 Tangerang from the beginning of the cycle was only 5%, in the first cycle it became 83.75% and in the second cycle it reached an average of 93.25%, and reached an average of 93.25%. The minimum target that has been set is 85%, meaning that 85% of teachers have been effective in setting Minimum Completeness Criteria. Thus, it can be concluded that through the workshop, teachers can improve the ability of teachers in setting Minimum Completeness Criteria at SMA Negeri 12 Tangerang.